Investigating the association between supraspinatus tendon abnormality, shoulder pain and isokinetic strength in elite swimmers: A cross-sectional study - So, B. C. L.; Lau, S. C. T.; Kwok, W. Y.; Tse, D. H. T.; Man, S. S. (Journal of Sports Science & Medicine, 2023)
Shoulder pain is common among elite swimmers due to the tremendous stress over shoulders during swimming. Supraspinatus muscle is one of the major prime movers and stabilizers of shoulder and is highly susceptible to overloading and tendinopathy. An understanding of the relationship between supraspinatus tendon and pain; and between supraspinatus tendon and strength would assist health care practitioners for developing training regime. The objectives of this study are to evaluate 1) the association between structural abnormality of supraspinatus tendon and shoulder pain and 2) the association between structural abnormality of supraspinatus tendon and shoulder strength. We hypothesized that structural abnormality of supraspinatus tendons positively associated with shoulder pain and negatively associated with shoulder muscle strength among elite swimmers. 44 elite swimmers were recruited from the Hong Kong China Swimming Association. Supraspinatus tendon condition was evaluated using diagnostic ultrasound imaging and shoulder internal and external rotation strength was evaluated by the isokinetic dynamometer. Pearson`s R was used to study the correlation between shoulder pain and supraspinatus tendon condition and to evaluate the association between isokinetic strength of shoulders and supraspinatus tendon condition. 82 shoulders had supraspinatus tendinopathy or tendon tear (93.18%). However, there was no statistically significant association between structural abnormality of supraspinatus tendon and shoulder pain. The results showed that there was no association between supraspinatus tendon abnormality and shoulder pain and there was a significant correlation between left maximal supraspinatus tendon thickness (LMSTT) and left external rotation/ concentric (LER/Con) and left external rotation/ eccentric (LER/Ecc) shoulder strength (p < 0.05) while internal rotation/ external rotation (IR/ER) ratio can also be a significant predicator on LMSTT >6mm (R2 = 0.462, F = 7.016, df = 1, p = 0.038). Structural change of supraspinatus tendon was not associated with shoulder pain, but could be a predictor on MSTT >6mm in elite swimmers.